Isolation and Characterisation of Staphylococcus aureus Strains from Phyllo Dough (Yufka) in Burdur Province - Sarigul, Nermin (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
In this study, 11 Staphylococcus aureus isolates were isolated and characterized by molecular methods from 50 phylo dough samples. Antimicrobial susceptibility testing against 12 antibiotics was performed by agar disk diffusion method and resistance was detected in 10 strains. 3 strains were oxacillin resistant which are also considered as methicillin-resistant S. aureus. Biofilm formation test were carried out by microplate test in TSB, TSB+1% sucrose, TSB+1% glucose, TSB+4% NaCl and BHI, BHI+1% sucrose, BHI+1% glucose and BHI+4%NaCl and biofilm formation detected in 4 strains. Coa, nuc and spa genes were evaulated for molecular identification. Enterotoxin A, B, C, D, and E genes, toxic shock syndrome toxin gene (tst) and mecA gene were investigated. MecA gene not detected, enterotoxin genes detected in 10 strains and tst gene detected in 9 strains. Our study confirmed that possible contamination and transmission of antibiotic resistant S. aureus from phyllo dough.